2015
DOI: 10.1007/s10561-014-9485-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of an acellular matrix from amniotic membrane for the synthesis of a human skin equivalent

Abstract: Human amniotic membrane (HAM) has useful properties as a dermal matrix substitute. The objective of our work was to obtain, using different enzymatic or chemical treatments to eliminate cells, a scaffold of acellular HAM for later use as a support for the development of a skin equivalent. The HAM was separated from the chorion, incubated and cryopreserved. The membrane underwent different enzymatic and chemical treatments to eliminate the cells. Fibroblasts and keratinocytes were separately obtained from skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…Owing to the thin thickness of sheep SIS, lower concentrations of reagents could be used which help to avoid the longer exposure time that supposed to have negative impact on the quality of the scaffold. Low concentrations of detergents have been used in a few studies which were mainly related to tissues, such as cornea, the AF vertebral disc, vessels and heart valves, and amniotic membrane with a long 24 and 72 h exposure time. Histological and immunohistological (H&E and DAPI) staining revealed that protocols used for decellularization of OSIS have been effective and a significant percentage of the cells were eliminated compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the thin thickness of sheep SIS, lower concentrations of reagents could be used which help to avoid the longer exposure time that supposed to have negative impact on the quality of the scaffold. Low concentrations of detergents have been used in a few studies which were mainly related to tissues, such as cornea, the AF vertebral disc, vessels and heart valves, and amniotic membrane with a long 24 and 72 h exposure time. Histological and immunohistological (H&E and DAPI) staining revealed that protocols used for decellularization of OSIS have been effective and a significant percentage of the cells were eliminated compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Four protocols were used to decellularize the BAM (Table 1). A control sample was kept without frozen treatment at −20 • C. For protocols I, II, and III, the separation of two layers, fetal and maternal, was performed as it is reported in most of the investigations [52][53][54][55]. On the other hand, this procedure was not performed in protocol IV, in order to observe variations in the properties of the membrane regarding exposure with the chemical solutions used and in cell culture.…”
Section: Decellularization Of the Bammentioning
confidence: 99%
“…104 Moreover, 1% trypsin-EDTA has been shown to result in complete elimination of epithelial and mesenchymal cells. 39 After decellularization, the acellular HAM retains all major structural components of the matrix and is biocompatible. There are no significant decreases in ultimate tensile strength, extensibility, and elasticity after decellularization.…”
Section: Decellularized Amniotic Membranementioning
confidence: 99%